Barriers and facilitators to housing and healthcare services for people experiencing homelessness with concurrent brain injury, mental health and substance use disorders: a qualitative study - Warren, Grace C.; Kennedy, Cole J.; Gavas, Nicholas; Schmidt, Julia; Woodin, Erica; Breese Biagioni, Janelle; Garcia-Barrera, Mauricio A. (Frontiers in Public Health, 2025)
BackgroundAcquired brain injury (ABI) can significantly impact mental health, vulnerability to addictions, and housing stability, yet the intersection of these challenges is understudied. Individuals living with ABI are disproportionately represented among populations experiencing homelessness and have a high prevalence of concurrent mental health and substance use (MHSU) disorders, leading to poorer health outcomes and lower quality of life. The objective of this study was to identify barriers and facilitators to housing and healthcare services for people experiencing homelessness with ABI and concurrent MHSU disorders.MethodsData were collected during a one-day workshop as part of the British Columbia Consensus for Brain Injury, Mental Health and Addiction project. Semi-structured focus groups involving ABI survivors, service providers, and community stakeholders explored barriers, facilitators, and recommendations for service improvements. Using manifest content analysis, data were analyzed in accordance with a well-validated conceptual framework for healthcare access.ResultsA total of 163 stakeholders (M = 46.40, SD = 13.80, 72% female) including 74 with lived experience of ABI and/or homelessness, participated in the focus groups. Manifest content analysis revealed five barriers and five facilitators: Barriers included (1) Stigma, (2) Insufficient Investment, (3) Siloed Systems, (4) Generalized Approaches to Housing, and (5) Policies that do not Support Complex Needs, while facilitators included (1) Increasing Discourse on the Intersections of ABI, MHSU, and Homelessness, (2) Government Commitment to Systemic Change, (3) Collaboration Across Organizations, (4) Community-Based Services, and (5) Supportive Housing Models.ConclusionsThese findings highlight gaps in existing policies and services while identifying effective approaches to supporting individuals experiencing these intersections. Efforts to address barriers and leverage existing facilitators may support the development of accessible services that address unmet health and housing needs among people experiencing homelessness with concurrent ABI and MHSU conditions.